2008
DOI: 10.1002/art.23698
|View full text |Cite
|
Sign up to set email alerts
|

Smad1 pathway is activated in systemic sclerosis fibroblasts and is targeted by imatinib mesylate

Abstract: Objective. Activation of Smad1 signaling has recently been implicated in the development of fibrosis. The goal of the present study was to gain further insights into activation of the Smad1 pathway in fibrosis in systemic sclerosis (SSc) and to determine whether this pathway is targeted by the antifibrotic drug imatinib mesylate.Methods. Levels of phosphorylated Smad1 and total Smad1 were examined in SSc and control skin biopsy samples by immunohistochemistry and in cultured fibroblasts by Western blotting. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 37 publications
2
55
1
Order By: Relevance
“…Thus, the TGF-␤-dependent synchronized regulation of the DNA binding activity of transcriptional activators, such as Smads, and repressors, such as Fli1, ultimately results in the increased expression of ECM genes. Clinical studies of cultured scleroderma fibroblasts and skin biopsies strongly support the primary role of TGF-␤ in the development of pathological fibrosis (3,18,22,29,30,40). The non-Smad signaling molecules, such as PKC ␦, represent attractive novel therapeutic targets for the treatment of this disease.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the TGF-␤-dependent synchronized regulation of the DNA binding activity of transcriptional activators, such as Smads, and repressors, such as Fli1, ultimately results in the increased expression of ECM genes. Clinical studies of cultured scleroderma fibroblasts and skin biopsies strongly support the primary role of TGF-␤ in the development of pathological fibrosis (3,18,22,29,30,40). The non-Smad signaling molecules, such as PKC ␦, represent attractive novel therapeutic targets for the treatment of this disease.…”
Section: Discussionmentioning
confidence: 94%
“…This small molecule inhibitor of intracellular kinase modulates the fibrotic process in SSc by interfering selectively with both TGF-β and PDGF signalling pathway (PDGFR/c-Abl and Smad1/ CCN2 pathway) [111,112]. In in vitro studies, the inhibition of the pathway results in a decrease in type I collagen and fibronectin-1 synthesis by dermal fibroblasts and myofibroblasts [113].…”
Section: Tyrosine Kinase Inhibitormentioning
confidence: 97%
“…Pannu et al [19] observed that activation of TGF-β-mediated Smad1 signaling occurs in a subset of SSc patients and contributes to persistent activation of SSc fibroblasts. This Smad1/CCN2 pathway is blocked by imatinib mesylate [19].…”
Section: Preclinical Evidence For the Treatment Of Fibrosis With Imatmentioning
confidence: 98%
“…Pannu et al [19] observed that activation of TGF-β-mediated Smad1 signaling occurs in a subset of SSc patients and contributes to persistent activation of SSc fibroblasts. This Smad1/CCN2 pathway is blocked by imatinib mesylate [19]. Bhattacharyya et al [18•] delineated a novel signaling mechanism of TGF-β and were able to position early growth response factor 1 downstream of c-Abl in a TGF-β-mediated fibrotic response of murine embryonic fibroblasts.…”
Section: Preclinical Evidence For the Treatment Of Fibrosis With Imatmentioning
confidence: 98%